Electrospinning of aligned nanofibers for biomedical application using a rotating drum collector - Wen, Jun Ham; Ching, Theng Koh (Microscopy Society of Malaysia (MSM), 2021)
Both random and aligned collagen fibers exist in extracellular matrix. The alignment of fiber in tissue engineering scaffolds can affect the cell morphology. Therefore, knowledge in the control of microstructure alignment in electrospun scaffolds is crucial. In this study, a rotating collector drum was designed and fabricated to collect aligned gelatin fibers using an electrospinning technique. The speed of the fabricated rotating drum collector was adjustable and controlled at 1000 rpm, 2000 rpm, and 3000 rpm. Electrospun scaffolds having aligned fibers were successfully produced using the rotating drum at 3000 rpm and compared with random nanofibers collected with the static plate. The speed of the rotating drum collector increased the alignment of the fibers and had little influence on fiber diameter. The results provide process parameters for the fabrication of aligned gelatin fibers.